Empowering Local Communities Through Digital-Based Sustainable Tourism Promotion in Nagari Air Bangis - Biru, Rembulan Catra Banyu; Setiawati, Merika; Frismelly, Arinda; Mardiansyah, Arischo (Universitas Negeri Padang, 2025)
This community service program addressed the limited digital promotion capacity of Nagari Air Bangis, a coastal tourism village in West Sumatra, which hindered its tourism growth despite its rich natural and cultural potential. Using a community-based participatory approach, the program was implemented through five stages: socialization, training, technology implementation, mentoring, and sustainability planning. The main activities involved training local residents to use and manage the Digitourism Nagari Air Bangis website as a digital platform for sustainable tourism promotion. Participants were trained to create digital content, manage online booking systems, and promote eco-friendly tourism practices while integrating local MSMEs into the platform. Qualitative descriptive analysis based on observation, documentation, and feedback revealed significant improvements in the community’s technical skills, awareness of sustainability, and motivation to manage tourism independently. The website became an effective medium for promoting destinations, local cuisine, and homestays, enhancing accessibility and service quality. Overall, the program successfully strengthened digital literacy, fostered community empowerment, and promoted sustainable tourism aligned with local economic and environmental values.